Single Photon Emission Computed Tomographic (SPECT) Study in Writer’s Cramp Patients (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Writer’s cramp is probably related to abnormal functioning of basal ganglia. But the actual mechanism is not known.Objective: The purpose of the present study was to evaluate the functional association of writer’s cramp with basal ganglia through SPECT study.Methodology: This prospective case control study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka and institute of nuclear medicine (INM), Dhaka from July 2001 to June 2003 to understand the basic pathophysiology of writer’s cramp by SPECT study and to compare the perfusion difference of basal ganglia between writer’s cramp and non-writer’s cramp group. A total of 20 respondents consisting of 10 in each group of writer’s cramp and non-writer’s cramp group as cases and controls respectively were enlisted by simple random method. Both the group of respondents underwent Tc99m HMPAO SPECT study during rest and writing period.Result: Out of 10 cases male patients were nine (90%) and female patient was one (10%) with male female ratio 9:1. Majority of patients presented third to fifth decades of which maximum (30%) were from 30-34 age group. Total six (60%) patients had simple writer’s cramp next three (30%) progressive writer’s cramp and one with dystonic variety. Maximum writer’s cramp patients were associated with great deal of writing (teacher, student, clerk, banker) and or performed repetitive hand movement (computer operator) from the point of occupational distribution. The perfusion difference of basal ganglia of both writer’s cramp and non-writer’s cramp group was seen by Tc99m HMPAO SPECT study during rest and writing period. First visual analysis of the scans by an expert nuclear medicine specialist showed no difference and then quantification of perfusion difference of basal ganglia by using SIEMENS macro programming environment (MPE) software showed no significant perfusion difference of basal ganglia between case and control group both during rest and writing period. In addition it was found highly significant perfusion difference (P=0.000321) separately in controls between left side and right side comparison during rest and significant difference (P=0.03) in writing and also significant in right side (P=0.022) during comparison of rest and writing period. The study also showed a significant perfusion difference (P=0.01) in cases between left and right comparison during writing and also significant perfusion difference (P=0.018) was found in rest and writing comparison of left side in writer’s cramp patients.Conclusion: There is no abnormality in basal ganglia perfusion pattern among the writer’s cramp patient.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 92-96